Programa Bolsa Família : o velho com novas roupagens - Ferreira, Nildete Virginia Turra (2010)
Analyzes the Family Grant Program (FGP), trying to check if its fast and steady growth - expressed in a significant increase in the amount of goals of care and resources invested - have resulted in substantial qualitative change in the nature of a focused, selective and compensatory program, of neoliberal bias. It also seeks to characterize the type of connection of the program with the current Brazilian Social Security System, especially with the consolidation of the Unified Social Services (USS) and the project of building a broader and universal Social Protection System in the country, founded on the notion of law. The FGP is identified as a program of social assistance in view of its characteristic of non-contributory program. The results confirm the idea that guided the investigation, that FGP, despite its massification, continues to be characterized as focused and rewarding, with intention to replace the universal social protection policies constituted as citizenship rights, being conducted autonomously and parallel to the USS. For the approach to the research object and obtaining the necessary information, the literature analyzing and the reading were used as the main methodological resources.